Scanning electron microscopy of tinea nigra - Isabelle Maffei Guarenti; Hiram Larangeira de Almeida Jr; Aline Hatzenberger Leitão; Nara Moreira Rocha; Ricardo Marques e Silva (Sociedade Brasileira de Dermatologia, 2014)
Tinea nigra is a rare superficial mycosis caused by Hortaea werneckii. This infection presents as asymptomatic brown to black maculae mostly in palmo-plantar regions. We performed scanning electron microscopy of a superficial shaving of a tinea nigra lesion. The examination of the outer surface of the sample showed the epidermis with corneocytes and hyphae and elimination of fungal filaments. The inner surface of the sample showed important aggregation of hyphae among keratinocytes, which formed small fungal colonies. The ultrastructural findings correlated with those of dermoscopic examination - the small fungal aggregations may be the dark spicules seen on dermoscopy - and also allowed to document the mode of dissemination of tinea nigra, showing how hyphae are eliminated on the surface of the lesion.